Pengaruh Penambahan ABS Bekas dan Jenis Plastik ABS Hasil Cetak Injeksi terhadap Umur Lelah - Syamsul Hadi; Dimas Kevin Alviano; Daffa Aureza Andhika; Ivan Rosdinata (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Many used ABS plastic wastes have problems in their management. The aim of this research is to obtain a prediction of the fatigue life of a mixture of ABS plastic and used ABS as an injection molding product. The research method is carried out through the stages of mixing used ABS with a volume of 10%, 20%, and 30% in ABS grade A and grade B; making fatigue test specimen molds according to R. R. Moore standards, injection molding of a mixture of used ABS and ABS grade A and grade B, checking the straightness and smoothness of the specimen surface, fatigue testing with increasing serial loads, analysis and making a graph of bending stress (S) against fatigue life (N) (S-N Curve). The results of the study showed that the addition of used ABS had an effect on the fatigue life of both grade A and grade B of ABS, where the fatigue life of grade A of ABS increased with the addition of the volume percentage from 0% -30% of used ABS with the highest value at the addition of 30%, namely 43698.9 cycles, while in grade B of ABS, the fatigue life decreased with the increase in volume from 0% -30% with the highest fatigue life in grade B of ABS plastic without a mixture or 0%, namely 41377.5 cycles, the implication of which is that the addition of 0% -30% of used ABS in grade A can increase the fatigue life, but grade B of ABS actually decreases its fatigue life.